Influence of Double Artificial Aging on Microstructure and Mechanical Properties of Semi Solid Aluminium Alloy 2024 - ขันทองคำ สิริพร; ศิวดำรงพงศ์ สมศักดิ์; ปลูกผล ธวัชชัย (Research on Modern science and Utilizing Technological Innovation Journal (RMUTI Journal), 2019)
The purpose of this research was to study the influence of one step artificial aging and two step aging on microstructure and mechanical properties of semi-solid aluminium alloy 2024. The samples were taken in solution heat treatment at 505 oC for 4 hours followed by quenching in the water at room temperature. The one step aging was carried out at 190 oC for 6, 9, 12, 15 and 18 hours, respectively. While, two step aging were initially aged at 110 oC for 8 h (first aging step) and then aged at 170 oC for 0.5, 1, 1.5, 2, 2.5, 3, 3.5 and 4 hours (second aging step), respectively. The microstructure of the samples was examined using the optical microscopy (OM). Hardness test (Rockwell scale B) and ultimate tensile strength were to evaluate mechanical properties. The results showed that at after artificial aging process the microstructure of semi-solid aluminium alloy 2024 consist of eutectic phase which distributed at the grain boundary of globular alpha-aluminium grain (α-Al). The one step aging at 190 oC for 15 hours provided both maximum hardness and ultimate tensile strength of 82.7 HRB and 395.3 MPa, respectively. As the same time, two step aging at initially on aged at 110 oC for 8 hours and then aged at 170 oC for 1 hour yielded both maximum hardness and ultimate tensile strength of 108 HRB and 415.70 MPa, respectively. It was obvious that both hardness and ultimate tensile strength of two step aging were higher than that of one step aging with and lesser time for artificial aging.